Core facets of divine forgiveness: a study across monotheistic religions - Paleari, Francesca Giorgia; Danioni, Francesca Vittoria; Valtulini, Valentina; Barni, Daniela; Sökmez, Aslı Bugay; Eissa, Sara; Greenwald, Yaakov; Knafo-Noam, Ariel; Regalia, Camillo (Frontiers in Psychology, 2025)
IntroductionAmong the religious factors that significantly contribute to believers’ well-being, research on the personal experience of divine forgiveness (DF) remains in its infancy. The aim of this study was to investigate similarities and differences in the conceptualization of DF, its conditional/unconditional nature, and the understanding of sin across the three main monotheistic religions.MethodsThis was achieved by interviewing theologians (N = 3) through a focus group and having lay believers (N = 229, 63.8% female, Mage = 33.09 years, SD = 13.81) from Christianity, Islam, and Judaism complete a self-report questionnaire.ResultsThe theologians’ and believers’ perspectives revealed that while there are shared aspects across religions (e.g., God’s mercy is greater than His justice), some differences are evident (e.g., the pathways to seek and achieve DF).DiscussionThese findings make a significant contribution to the psychology of religion, shedding light on universal and culturally specific dimensions of this multidimensional phenomenon.